Analisis Sektor Unggulan di Kabupaten Gunungkidul - Jurni Hayati; Asep Yusup Hanapia; Jumri Jumri; Aso Sukarso; Dwi Hastuti Lestari Komarlina; Asep Muhammad Adam (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
This study aims to identify basic and non-basic sectors, analyze competitive and less competitive sectors, and determine leading sectors in Gunungkidul Regency, Special Region of Yogyakarta Province. The study uses secondary data in the form of Gross Regional Domestic Product (GRDP) of Gunungkidul Regency and GRDP of Yogyakarta Special Region Province for the period 2021–2025 obtained from the Central Statistics Agency (BPS) of Yogyakarta Special Region Province. The analysis was conducted using the Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ), and overlay analysis methods. The results of the SLQ analysis indicate that there are seven basic sectors in Gunungkidul Regency, namely the agriculture, forestry, and fisheries sector; the mining and quarrying sector; the water supply, waste management, and recycling sector; the wholesale and retail trade sector; the transportation and warehousing sector; the government administration, defense, and mandatory social security sector; and other service sectors. Meanwhile, the results of the DLQ analysis indicate that there are twelve sectors that have competitive capabilities, namely the agriculture, forestry, and fisheries sector; mining and quarrying sector; manufacturing industry sector; water supply, waste management, waste, and recycling sector; wholesale and retail trade sector; information and communication sector; financial services and insurance sector; real estate sector; corporate services sector; education services sector; health services and social activities sector; and other service sectors. Based on the results of the overlay analysis, it can be concluded that Gunungkidul Regency has five leading sectors, namely the agriculture, forestry, and fisheries sector; mining and quarrying sector; water supply, waste management, waste, and recycling sector; wholesale and retail trade sector; and other service sectors.